2log3 от (х-2) + log 3 от (х-4)^2=0

2log3 от (х-2) + log 3 от (х-4)^2=0
Гость
Ответ(ы) на вопрос:
Гость
  [latex]2log_3(x-2)+log_3(x-4)^2=0, \\ \left \{ {{x-2>0,} \atop {(x-4)^2>0,}} \right. \\ \left \{ {{x>2,} \atop {x-4\neq0,}} \right. \\ \left \{ {{x>2,} \atop {x\neq4,}} \right. \\ 2log_3(x-2)+2log_3(x-4)=0, \\ log_3(x-2)+log_3(x-4)=0, \\ log_3(x-2)(x-4)=log_31, \\ (x-2)(x-4)=1, \\ x^2+6x+7=0, \\ D_1=3^2-7=2, \\ x_1=-3-\sqrt2<0<2,\\ x_2=-3+\sqrt2<0<2;[/latex] действительных корней нет.
Не нашли ответ?
Ответить на вопрос
Похожие вопросы